THE SELF-EFFICACY SCALE OF THE FIFTH SEMESTER STUDENTS IN ONLINE LEARNING - Suryanovika, Citra (Jurnal Ilmiah Spectral, 2022)
The study discusses the self-efficacy of STBA Pontianak students in online learning during the covid-19 situation. The study involved 34 fifth-semester students of STBA Pontianak enrolled in learning theories subject. The study was a quantitative design. It used a questionnaire referring to the New General Self- Efficacy Scale (NGSES) of Chen, Gully, & Eden (2001). The online questionnaire contains eight variables, and five response categories of the Likert scale is distributed. The study found that the mean was 29,3, while the standard deviation was 5,1. The responses toward all 8-item NGSES were varied. The first variable had the highest mean. The overall figure showed that the students had a high self -efficacy scale in implementing online learning during the Covid-19.